MiR-15a-5p targets FOSL1 to inhibit proliferation and promote apoptosis of keratinocytes via MAPK/ERK pathway. Issue 4 (November 2021) - Meng, Jian; Chen, Fang-Ru; Yan, Wen-Jie; Lin, You-Kun
Abstract: Aim: Our goal of this study is to explore the effects of miR-15a-5p on keratinocyte proliferation and apoptosis, as well as the underlying molecular mechanisms. Materials and methods: The gene expression of miR-15a-5p in healthy and psoriatic tissues was evaluated by qRT-PCR. Interleukin 22 (IL-22) was used to stimulate in vitro keratinocyte hyperproliferation, and the effect of miR-15a-5p knockdown/overexpression was assessed. The binding between miR-15a-5p and FOSL1 was predicted with bioinformatic database and confirmed with luciferase reporter assay. Keratinocyte viability, proliferation and apoptosis with different treatments were evaluated by MTT assay, colony formation, and flow cytometry, respectively. The proliferative, apoptotic, and MAPK/ERK signature proteins were evaluated with western blot. Results: The miR-15a-5p expression was significantly downregulated in psoriasis patients. In vitro psoriasis model was developed by IL-22 stimulation, which enhanced proliferation and reduced apoptosis of keratinocytes. MiR-15a-5p overexpression suppressed IL-22-induced proliferation and induced apoptosis. Bioinformatics analysis and luciferase reporter assay showed miR-15a-5p bound to FOSL1. FOSL1 knockdown inhibited IL-22-induced proliferation and enhanced apoptosis of keratinocytes. Keratinocyte proliferation was further enhanced by IL-22 stimulation with FOSL1 overexpression, and miR-15a-5p overexpression reversed the hyperproliferation and provoked keratinocyte apoptosis. MiR-15a-5p/FOSL1 functioned via MAPK/ERK pathway. Conclusion: In the current study, we reported miR-15a-5p exhibited anti-proliferative and pro-apoptotic effects on keratinocytes using an IL-22-induced cells as in vitro psoriasis model. The results showed miR-15a-5p could be used as potential biomarker to treat psoriasis. Highlights: MiR-15a-5p gene expression was suppressed in psoriatic tissues. MiR-15a-5p overexpression inhibited IL-22-induced keratinocyte proliferation. MiR-15a-5p overexpression induced keratinocyte apoptosis. MiR-15a-5p directly binds to FOSL1 to regulate keratinocyte proliferation via MAPK/ERK pathway.